Sistem Informasi Akuntansi Pelayanan Jasa Rawat Jalan Dan Rawat Inap Pasien Umum Pada Rumah Sakit X Surabaya - Shamilatus Zakia; Rika Yuliastuti (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Hospitals need an integrated accounting information system to manage complex financial transactions in outpatient and inpatient services. This study aims to analyze the implementation of the accounting information system at Hospital X Surabaya and identify obstacles and solutions to improve its effectiveness. The research method uses a qualitative descriptive approach through case studies with data collection techniques in the form of interviews, direct observation, and document analysis. The results of the study show that the Hospital Management Information System implemented since 2019 has succeeded in increasing operational efficiency by reducing billing time from 15 minutes to 3 minutes and reducing recording errors from 5% to 0.5%. However, there are obstacles in the form of limited server capacity during peak hours, limited customization features, and dependence on internet connections. The study recommends improving server infrastructure, developing customization features, implementing an automatic backup system, and ongoing training to improve system effectiveness.